1983
DOI: 10.1530/acta.0.1020277
|View full text |Cite
|
Sign up to set email alerts
|

Loss of serum transcortin in human shock associated with severe infection by candida albicans

Abstract: The cortisol binding ability of transcortin (corticosteroid binding globulin or CBG) was found to be virtually absent from the sera of patients in a state of shock associated with high levels of antibodies to candida albicans.At the same time the serum proteins of the patients in shock displayed a number of the classical responses seen in acute inflammation: increased haptoglobin (28 \m=+-\10 vs 10.8 \m=+-\7.7 \g=m\m in normals), reduced prealbumin (1.7 \m=+-\ 0.6 vs 3.6 \m=+-\0.1 \g=m\m in normals) and albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…septic shock (Zouaghi, Savu, Delorme et al 1983), where the CBG cortisol binding capacity appears to be very low. Serum concentrations of CBG generally increase in women taking various forms of oral contraceptives, almost to the same extent as observed during preg¬ nancy, and this is thought to be due to the induction of hepatic CBG synthesis by oestrogens.…”
Section: Discussionmentioning
confidence: 99%
“…septic shock (Zouaghi, Savu, Delorme et al 1983), where the CBG cortisol binding capacity appears to be very low. Serum concentrations of CBG generally increase in women taking various forms of oral contraceptives, almost to the same extent as observed during preg¬ nancy, and this is thought to be due to the induction of hepatic CBG synthesis by oestrogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas a high carbohydrate diet causes a 35-40% increase in plasma SHBG, plasma CBG falls by about 20% under the same conditions (40). As already mentioned plasma CBG decreases drastically in septic shock (12,13). Doe et al (41) made the interesting observation that CBG was depressed in pernicious anemia, but not folate deficiency, and that treatment of the disease with vitamin B 12 reversed the change within 2 weeks.…”
Section: Rosnermentioning
confidence: 93%
“…Although there is little direct evidence to support this sequence of events in stress, neither is there a convincing counterexample. Indeed, in certain types of stress, CBG rapidly disappears from plasma (12,13); although that observation can be interpreted in a number of ways, it is compatible with CBG freeing all of its bound hormone and making it rapidly available. A probable mechanism for the rapid disappearance of CBG has been published (14) and lends support to this view of the biology (see below).…”
Section: Introductionmentioning
confidence: 99%
“…In the first study concerning this question, subcutaneous turpentine injections to 2-monthold rats were shown to induce a 3-fold decrease in serum corticosterone binding [36]. Subsequent investigations by the same group found that serum CBG binding capacity was lower during severe infection [37] and septic shock [38]. Recently, this latter finding was confirmed by ra dioimmunoassay of CBG [39].…”
Section: Inflammationmentioning
confidence: 98%